2007
DOI: 10.1021/bc070110w
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Relaxation Switch Detection of Human Chorionic Gonadotrophin

Abstract: Functionalized nanoparticle contrast agents, also known as magnetic relaxation switches (MRS), were prepared to detect protein A and the beta subunit of human chorionic gonadotrophin (hCG-beta). Antibodies were attached to cross-linked iron oxide (CLIO) nanoparticles using standard peptide chemistry. Protein A was used as a simple model analyte, as it is naturally multivalent and can bind multiple CLIO-IgG simultaneously. The addition of PA to CLIO-IgG resulted in transverse relaxation time (T2) shortening com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 18 publications
1
47
0
Order By: Relevance
“…“Clickable” cross-linked iron oxide (CLIO) NPs are also appropriate for MRS applications because they are sufficiently stable to permit a variety of surface chemistries [51, 52]. CLIO surfaces have been designed to detect ions [53], DNA [46, 50, 54], proteins [50, 54, 55] and bacteria, as well as mammalian cells [56]. A particularly valuable system for the study of MRS is the reaction of NPs displaying the Tag peptide and reacting to a monoclonal antibody (anti Tag) binding to the peptide [48].…”
Section: Bioanalytical Analysis Technologiesmentioning
confidence: 99%
“…“Clickable” cross-linked iron oxide (CLIO) NPs are also appropriate for MRS applications because they are sufficiently stable to permit a variety of surface chemistries [51, 52]. CLIO surfaces have been designed to detect ions [53], DNA [46, 50, 54], proteins [50, 54, 55] and bacteria, as well as mammalian cells [56]. A particularly valuable system for the study of MRS is the reaction of NPs displaying the Tag peptide and reacting to a monoclonal antibody (anti Tag) binding to the peptide [48].…”
Section: Bioanalytical Analysis Technologiesmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] Recently, our group proposed and demonstrated combining PSi with biologically functionalized nanometer superparamagnetic beads (SPBs) for rapid and one-step immunoassaying. 29 surfaces of SPBs including DNA, RNA, anti-body and anti-gen. [33][34][35][36][37][38][39] Furthermore, utilizing SPBs has many advantages over non magnetic counterparts including magnetically induced collection, manipulation and immobilization, a stable magnetic signal that permeates liquids and surrounding materials, and large surface area. [40][41][42] Pil Ju Ko received his Ph.D. degree in Electrical and Electronic Engineering from Tokyo Institute of Technology, Japan (2012).…”
Section: Introductionmentioning
confidence: 99%
“…While iron oxides (magnetite [Fe 3 O 4 ] and maghemite [␥ -Fe 2 O 3 ]) have been utilized for magnetic separations for fifty years, it was not until 1978 that Ohgushi demonstrated that they were capable of shortening the relaxation times of water in a controlled and useful manner [2]. Aside from their use in magnetic resonance imaging (MRI), iron oxide nanoparticles have been used in a number of other applications, including hyperthermia [3,4], as spoilers in magnetic resonance spectroscopy [5], and as sensors for metabolites and other biomolecules [6][7][8][9][10]. In this chapter we discuss the targeting of multifunctional multimodal magnetic nanoparticles, including the relevant chemistries and properties of iron oxides by doping the particle core with dicationic metal ions, such as Co 2+ , Fe 2+ , Mn 2+ , or Ni 2+ [15].…”
Section: Introductionmentioning
confidence: 99%